2017
DOI: 10.20518/tjph.375326
|View full text |Cite
|
Sign up to set email alerts
|

State and trait anxiety levels among mothers of inpatient children and related factors

Abstract: ÖzetAmaç: Bu araştırma, hastanede yatarak tedavi gören çocukların annelerinde, durumluk ve sürekli anksiyete düzeyini ve çeşitli tıbbi ve sosyo-demografik faktörlerin bu düzeylere etkisini belirlemek amacıyla yapılmıştır. Yöntem: Tanımlayıcı olan araştırma 2016 yılında Erciyes Üniversitesi Çocuk Hastanesinde yapılmış; hastanenin çeşitli servislerinde yatmakta olan çocukların anneleri araştırma kapsamına alınmıştır. Annelerle (158 anne) hastane ortamında görüşülerek, sosyo-demografik anket formu ve Durumluk-Sür… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 10 publications
(8 reference statements)
1
4
0
Order By: Relevance
“…Moreover, as one can see in Table 5, the patient children’s trait anxiety scores were significantly higher than their state anxiety points ( P =0.37). This is in conformity with the literature, which states that hematology-oncology disease raises trait anxiety due to reasons such as fear of death, frequent hospitalizations, and the physical burdens of treatment 20,21. The literature also states that parents of children with a hematology-oncology disease are more anxious and stressed 22,23.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Moreover, as one can see in Table 5, the patient children’s trait anxiety scores were significantly higher than their state anxiety points ( P =0.37). This is in conformity with the literature, which states that hematology-oncology disease raises trait anxiety due to reasons such as fear of death, frequent hospitalizations, and the physical burdens of treatment 20,21. The literature also states that parents of children with a hematology-oncology disease are more anxious and stressed 22,23.…”
Section: Discussionsupporting
confidence: 86%
“…This is in conformity with the literature, which states that hematology-oncology disease raises trait anxiety due to reasons such as fear of death, frequent hospitalizations, and the physical burdens of treatment. 20,21 The literature also states that parents of children with a hematology-oncology disease are more anxious and stressed. 22,23 However, in this study, no significant difference was found between the trait anxiety scores of healthy children's parents and patient children's parents.…”
Section: Discussionmentioning
confidence: 99%
“…Gonener and Pek also showed that parents became anxious when they heard their children were hospitalized and when their children stayed in hospital (Gonener and Pek, 2009). Similarly, Günay et al reported that mothers whose children stayed in hospital had high state and train anxiety levels (Gunay et al, 2017) and that their children's becoming ill and staying in hospital was an important source of fear for the mothers.…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Sen-Beytut et al, children were found to picture hospital as something negative and have a higher rate of depression and low self-esteem (Sen-Beytut et al, 2009). Although psychosocial functions of parents are important for physical and mental health outcomes of children (Commodari, 2010), hospitalization of children affects parents as much as children (Aykanat and Gozen, 2014;Celebi et al, 2015;Gunay et al, 2017). Treatment of children in hospital causes parents to think their children have a severe health problem.…”
Section: Introductionmentioning
confidence: 99%
“…mothers according to the person who taught the steam application to them, and the mean scores of the mothers who received training from a doctor were significantly higher than those of who received training from a nurse.Results of a study conducted with parents whose babies were hospitalized shows that the information and support provided by a doctor or nurse reduce anxiety and stress(29)(30)(31). During nursing care, the lack of information regarding the health and needs of the patient should be determined and eliminated.…”
mentioning
confidence: 99%